Global Elderly Migrations and Their Impact on Health Care Systems - Tomasz Holecki; Anna Rogalska; Karolina Sobczyk; Joanna Woźniak-Holecka; Piotr Romaniuk (Frontiers Media S.A., 2020)
Demographic transitions that occur in decreased dynamics of natality and rising number of elderly in population structures constitute a challenge for all national economies. Another global phenomena are large-scale migration processes driven by intensification of globalization process, development of technologies, and telecommunications. Although both these phenomena were vastly addressed in many ways in scientific literature, a notifiable fact is that there are only few researches that would investigate them in connection and consider migration of older people and its consequences, especially for health systems. Despite the fact that generally the likelihood of migrations reduces along with age, in some countries a higher share of migrants older than 65 years in reference to the entire group of migrants are being observed. It is the more essential that groups of seniors represent an increasing percentage of people. There are also differences in between standard reasons for migrations in young people and the factors affecting migrations in elderly ones. Many variables can influence migration decisions among older people, and they can be affected by seniors' health conditions, levels of health care within the target countries they migrate to, and the living standards. Such factors as population aging, reduced fertility, and international migration have affected the changes in demographic profiles of many countries. The consequence of migration decisions in the group of seniors is, among others, the impact on health care systems of single nation states, which are more and more important elements of economic, social, and financial systems.